TONI MORRISON E CAROLINA MARIA DE JESUS: DOIS TIMBRES MARCANTES DA VOZ AUTORAL FEMININA - Nascimento, Cleideni Alves do (2012)
This research aims to reflect on the relation between reading and writing and how the contact with engaged literature (SARTRE, 1989) has the power of changing a person’s identity, giving him/her an own voice. This voice would allow him to think and speak about himself, providing the person autonomy as subject. Nevertheless, this research emphasis is limited to the analysis of the authorial voice, the writer’s voice (ALVAREZ, 2006). On this purpose, the voices of two great writers of the 20th century were chosen - the North American Toni Morrison and the Brazilian Carolina Maria de Jesus. They overcame the adversities of their respective social contexts and got notability through their writing. As in a circular movement, it is noticed that reading and writing are not separable (BARTHES, 1970) and by analyzing the relation both writers have with reading, it is expected to show they developed their voices while writers, exactly because they were readers. For analyzing their authorial voices, their first books were chosen: the novel The Bluest Eye (2003) by Morrison and the diary “Quarto de Despejo”(2007) by Carolina Maria de Jesus. It is believed that even in the most contrary situations and in groups socially discriminated, literature can act a humanizing role (CÂNDIDO, 2004; PETIT, 2009; TODOROV, 2010) and make those people conscious about themselves and about the world around them, helping them live better. Literature would have done that for the researched writers. As the conclusion, it is noticed that Morrison’s and Jesus’s authorial voices stand out by their authenticity and engagement with social matters, but also by the work of aesthetical elaboration. Their writings would act on the reader on the same way other writers’ work acted on them.